Concept connection strategy to develop higher-order thinking in geography courses - Yani Ahmad; Mulyadi Asep; Rosita Rosita (E3S Web of Conferences)
The Connecting Concepts learning strategy is a logic game that asks students to connect two or more to form a logical narrative. The formation of a narrative that emerges from two concepts that are brought together is at the level of high order thinking (HOTS) in Bloom-Anderson’s taxonomy. This research uses a quasi-experimental method with a pre-post test design. The sample was second grade high school students from three high schools in Sumedang, West Java Province, Indonesia (n=160). An independent t-test revealed significant differences in the mean scores on the pre-test in favor of the post-test (p < 0.05). It is concluded that the concept connection strategy has the potential to develop high-level thinking skills because it can increase students’ creative thinking.